Pengaruh Aplikasi Pembelajaran Pengenal Aksara Bali Terhadap Prestasi Belajar Siswa Kelas III pada Mata Pelajaran Bahasa Bali di SD Negeri 1 Kawan - Sulaksana, Putu Arya; Agustini, Ketut; Pradnyana, I Made Ardwi (Universitas Pendidikan Ganesha, 2021)
This study aims to, 1) determine the effect of the learning application identifier Balinese script towards student achievement in Balinese subjects in SDN 1 Kawan. 2) describe the students' responses regarding the learning of Wianjana scripts using the learning media of the introduction of Balinese script. As an application for learning Balinese alphabet recognition, a template matching technique is used. This type of research is quasi-experimental research (quasi-experimental) with a post-test-only control group design. The population of this study was all students of class III of SD Negeri 1 Kawan, totaling 42 students. The sampling technique in this study is used the saturated sampling technique because all members of the population are members of the sample. The sample consisted of class III-A of 21 students as the experimental group and class III B of 21 students as a control group. Data were collected using a multiple-choice test method and a questionnaire method. A multiple-choice test is given about 20 items. The research questionnaire used was a questionnaire with a gutter scale, where respondents answered questions about the number of answer choices provided. The data analysis method uses descriptive qualitative and quantitative data analysis. Hypotheses test using correlated sample t-tests. The results showed that 1) The application of learning the introduction of Balinese Script teaches students' learning achievement in the Balinese subject at SD Negeri 1 Kawan elementary school. This can be seen from the approval of the average score of students' learning achievement tests in the study group is greater than the control group. 2) The students' responses about the learning of Wianjana scripts using the learning media for the introduction of Balinese script were very positive. Can be seen from the results of the questionnaire which shows the figure of 88.57% with a very positive category.